NON PHARMACOLOGICAL THERAPY OF ANXIETY IN PREGNANT MOTHERS IN THE ERA OF THE COVID-19 PANDEMIC: LITERATURE REVIEW - Primasari Mahardhika Rahmawati; Nisa Nabila Azmi; Sri Wahyuningsih; Musviro Musviro (Indonesian Journal of Health Care Management, 2021)
Introduction : The cause of the third trimester pregnant women in the Covid-19 Pandemic Era experiencing anxiety, namely concerns related to growth, development, neonatal, a reduction in the frequency of pregnancy checks, and delays in classes for pregnant women. If pregnant women experience anxiety that is not immediately addressed, there will be an increased risk of congenital abnormalities in the form of failure to close the cleft palate, the risk of caesarean section surgery, delivery with tools, premature birth, babies born with low birth weight, and in the long term it is associated with behavioral and emotional disorders in children. In this case, Relaxation of muscle progressive is a kind of therapy for pregnant women.Methode : The method used in the preparation of the literature review uses the PRISMA checklist to determine the selection of the studies found and adapted to the purpose of the literature review. Search literature in this literature review using several electronic databases including Scholar, Pubmed, and Springer Link.Result : The result from literature review shows that muscle progressive relaxation, Yoga, Dzikir, listening Murrotal Al-Qur’an and Lullaby music are able to reduce the anxiety of pregnant women in the Covid-19 Pandemic era. For further research will be explain non-pharmacological therapy anxiety of Covid-19 for pregnant woman starting in the 1st  and 2nd trimesters pregnancy.Conclusion : Can be used as research material by using the keywords (therapy) AND (anxiety) AND (pregnant woman) AND (covid-19). Further research can explain nonpharmacological therapy for anxiety in pregnant women starting in the 1st, 2nd trimester of pregnancy in anxious cases with Covid-19.Keywords: Non-pharmacology therapy; therapy; anxiety; pregnant woman; COVID-19